Learning Transformation: The Influence of Project-Based Learning on Students' Interest and Achievement in Indonesian Language - Ilma Rahim; Kembong Daeng; Ita Rosvita (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze the influence of the Project-Based Learning (PjBL) method on students' interest and learning outcomes in Indonesian language education at the Faculty of Economics, Universitas Patompo. The research employs a qualitative descriptive method with a triangulation approach, encompassing source, method, and theory triangulation. The sample includes 60 management students from the 2023 cohort, selected using Cochran's formula for a limited population with a 95% confidence level and a 5% margin of error. Data were collected through questionnaires completed by students after implementing the PjBL method and analyzed descriptively. The results show that the application of PjBL significantly enhances students' learning interest, with 52.6% strongly agreeing and 42.1% agreeing that they were more engaged in learning Indonesian through PjBL. Additionally, 63.2% agreed and 36.8% strongly agreed that their understanding of Indonesian language materials improved after PjBL implementation. Factors such as interactivity, the relevance of projects to real life, and collaboration among students contributed to increased interest and learning outcomes. This research contributes to curriculum development in higher education, particularly in Indonesian language learning, and offers practical insights for lecturers in designing more effective teaching strategies. Future studies are recommended to broaden the scope of subjects and populations studied and to investigate the long-term impact of PjBL on students' academic and professional outcomes.